NANOBIOTECHNOLOGY IN THE TREATMENT OF LEISHMANIA SPP. - Bastidas Pahceco, Gilberto Antonio (2020)
Leishmaniasis is a major public health problem due to the high morbidity and mortality that it has worldwide with a tendency to increase cases and spread of infection at diff erent latitudes. Besides, the number of chemotherapeutic agents is small, its toxicity is high and when its toxicity is reduced, bioavailability also reduces the success of vaccination strategies. It is here that the design of nanotechnology-based drug delivery systems turns out to be a promising strategy in the treatment of this parasite. Th e objective of this paper was to show relevant information on nanotechnology applied to the treatment of leishmaniasis as an innovative tool for the control of this disease. Th rough the review of scientific literature in databases based on descriptors or related keywords. Th e paper was structured in fi ve sections to facilitate reading and analysis: pharmacological treatment still recommended and a small introduction to vaccines against leishmaniasis, application of nanotechnology in human health, the case of leishmaniosis, aspects that are pointed out in nanomedicines for better its eff ectiveness, vaccines against leishmaniasis in nanotechnology, and conclusions. It is concluded that nanobiotechnology, specifi cally nanoparticles, is an excellent tool for introducing the active substance of drugs into infected cells during the pathological process produced by the parasite of leishmaniasis.